FINANCIAL CRISIS AND THE CENTRAL BANK SYSTEM - Richard POSPISIL; Serghei MĂRGULESCU (Challenges of the Knowledge Society)
The financial crisis that began in 2008 gradually developed into a global economic crisis and continues to this day. There is a lot of causes standing behind the creation, depth and process of the crisis, which is the deepest since the thirties of last centrury. One of the reasons can be found in the risky behavior of commercial banks, especially in the excessive lending of credits and mortgages. Its share on the financial crisis have central banks and their failure as the financial supervisory authority. But there is a lot of another causes of failures in the commercial banking system. And some of the causes lies outside the banking system and monetary policy. Its share of the blame has also become from state and its expenditure on the social policy.This article analyzes the role of the commercial banking system and the central banks on the financial crisis including prevention options and measures.